Platelet-to-Lymphocyte Ratio as Marker of Platelet Activation in Patients on Potent P2Y Inhibitors - Patricia P. Wadowski MD, PhD; Joseph Pultar; Constantin Weikert; Beate Eichelberger; Maximilian Tscharre MD, PhD; Renate Koppensteiner MD; Simon Panzer MD; Thomas Gremmel MD, MBA (Journal of Cardiovascular Pharmacology and Therapeutics, 2022)
A high platelet-to-lymphocyte ratio (PLR) has recently been associated with ischemic outcomes in cardiovascular disease. Increased platelet reactivity and leukocyte-platelet aggregate formation are directly involved in the progress of atherosclerosis and have been linked to ischemic events following percutaneous coronary intervention (PCI). In order to understand the relation of PLR with platelet reactivity, we assessed PLR as well as agonist-inducible platelet aggregation and neutrophil-platelet aggregate (NPA) formation in 182 acute coronary syndrome (ACS) patients on dual antiplatelet therapy with aspirin and prasugrel (n = 96) or ticagrelor (n = 86) 3 days after PCI. PLR was calculated from the blood count. Platelet aggregation was measured by multiple electrode aggregometry and NPA formation was determined by flow cytometry, both in response to ADP and SFLLRN. A PLR ≥91 was considered as high PLR based on previous data showing an association of this threshold with adverse ischemic outcomes. In the overall cohort and in prasugrel-treated patients, high PLR was associated with higher SFLLRN-inducible platelet aggregation (67 AU [50-85 AU] vs 59.5 AU [44.3-71.3 AU], P = .01, and 73 AU [50-85 AU] vs 61.5 AU [46-69 AU], P = .02, respectively). Further, prasugrel-treated patients with high PLR exhibited higher ADP- (15% [11%-23%] vs 10.9% [7.6%-15.9%], P = .007) and SFLLRN-inducible NPA formation (64.3% [55.4%-73.8%] vs 53.8% [44.1%-70.1%], P = .01) as compared to patients with low PLR. These differences were not seen in ticagrelor-treated patients. In conclusion, high PLR is associated with increased on-treatment platelet reactivity in prasugrel-treated patients, but not in patients on ticagrelor.